Free Trade Agreement and Non-Tariff Measure on Indonesia’s Export Performance: Major Export Destination Countries - Untung Perdamayan (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2023)
The study in this paper aims to estimate the effect of Free Trade Agreement (FTA) and Non-Tariff Measures (NTMs) on trade volume in Indonesia. The methodology used to determine the effect of the FTA and NTMs is the Fixed Effect Model (FEM) and Random Effect Model (REM) on a panel dataset from 2000 to 2020 in 10 main export destination countries for Indonesia, and it sets four models to explain these effects. Models 2 to 4, which use the fulfillment of SPS, TBT, and a combination of SPS and TBT as non-tariff barriers variables, are found to have a negative and significant effect on Indonesia’s export performance, with the result that SPS requirements by importing countries will be reduced by 5.7% (Model 2), TBT requirements by 6.02% (Model 3), and the combination of fulfilling SPS and TBT requirements by 8.4% (Model 4) on Indonesia’s export performance. In the REM model, RTA as a variable of FTA has a negative and significant impact on the value of Indonesia’s exports with 3.8% effects. RTA policies with several countries such as Japan, Singapore, and South Korea have not been effective in increasing Indonesia’s exports for several periods. Meanwhile, the trade between the USA and Indonesia without an FTA mechanism has actually increased the value of exports from 2003 to 2020. Furthermore, the implementation of meeting the requirements of non-tariff barriers could have a negative effect on Indonesia’s export performance, and trade relations occur with four countries with the largest and negative intercept effect, namely Japan, followed by Singapore, USA, and South Korea.